(untitled) (Community Based Medical Journal, 2016)
This descriptive type of cross-sectional study of 72 cases of uterine rupture was conducted over 1 year (from September 2006 to August 2007) in the department of Obstetrics and Gynaecology, Mymensingh Medical College Hospital, Bangladesh to evaluate the maternal outcome of different types of surgery, to assess the maternal mortality and maternal morbidity. All cases of ruptured uterus which were received & treated and did not die within 30 minutes of admission are included in the study. Data were collected by preformed data collection sheet. The results showed that the common age groups were between 20-30 years in 31(68.00%) cases. Among all ruptured cases, 6 cases (8.33%) were Primigravida, 52 cases (72.22%) were between gravida 2nd to 4th and 14 cases (19.44%) were gravida 5th or above. Among all cases, 66 cases (91.66%) required blood transfusion; Subtotal hysterectomy was done in 36 cases (50.00%), total hysterectomy in 4 cases (5.56%), and repair of the rent in 32 cases (44.44%). Associated operations were done along with repair or hysterectomy in 13 (18.05%) cases. Postoperative complications were found in 23 (31.94%) cases. The shortest stay was 8 days & the longest stay was 62 days. The hospital staying was about 2 weeks in 48(66.70%) cases. Among 10 death cases (13.90%) maximum patient died within first 5 hours. The causes of maternal death were due to septicemia, renal failure and shock in 20%, 30% and 50% respectfully. CBMJ 2016 January: Vol. 05 No. 01 P: 20-26